THE TIME OF APPERANCE OF POSTPARTUM ESTRUS VARIOUS PARITIES IN BALI CATTLE - Muslimin, Muhammad Ihwanul; Laksmi, Desak Nyoman Dewi Indira; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2022)
Parity is a period in the process of animal recycling with an indication of the number of partis of livestock. This research discusses to study the time of postpartum esterus in Balinese cattle with various parities. This research was an observational analytic study with a cross-sectional study design. The analysis used in this research is descriptive analysis. Samples used in this study were 21 cows with various parity added 7 cows with 1 calf, 7 cow with 2 calves and 7 cows with more than 2 calf. The results showed that cows with various parities increased the post parturition estrus delay due to the difficulty in obtaining feed. From these results it can be concluded that there are differences in post partus estrus in various parity I, II and III due to lack of optimal management in maintenance, especially in terms of feed. It should be noted again in the management of maintenance, especially feed to optimize the reproductive function of the animal.